0433 Towards an ideal national work-related ill health surveillance system in great britain. (21st August 2017) - Chen, Yiqun; Fishwick, David; Curran, Andrew
Abstract : Population-based occupational health surveillance includes work-related ill health surveillance and workplace health risk exposure surveillance. It is an important intelligence gathering system at the national level, which supports the planning, monitoring and evaluation of measures to prevent work-related ill health. The intelligence is essential for targeted intervention, prioritisation, tracking progress and evaluation of impact. To make best use of resources for intelligence gathering, the approaches used should be regularly assessed and monitored to ensure they remain fit-for-purpose, cost-effective and forward looking. In the context of the strategic approach for research planning and prioritisation in the Health and Safety Executive (HSE), a series of workshops were developed. One of the HSE internal workshops was organised in January 2017. Some, 26 (90%) of the 29 invited stakeholders have participated to develop a common vision for a population-based work-related ill health surveillance system that will continue to meet HSE's intelligence needs now and in the future; Following detailed assessments of the gaps in the current system, a wide range of innovative approaches were explored. Some practical first steps to improve the system were recommended with an emphasis on more systematic and strategic data collection. The key characteristics of an ideal system were also identified, including new features on case investigation and detecting new/emerging work-related ill health risks to inform timely preventative actions. The outputs of the workshop are presented. They have informed HSE priorities in the continued development of the system to support its mission to prevent work-related ill health.